Impact of Perceived Supervisor Support and Rewards and Recognition Toward Performance Through Work Satisfaction and Employee Engagement in Employee Marketing Banks - Rahma Kurniawan; Rina Anindita (Business and Entrepreneurial Review, 2021)
The company as an organization has a dependency on individuals within the company itself. Employees as individuals in the company are part of the organizational structure that has a major role in determining the achievement of company goals. In the perspective of employees, direct supervisors' attitudes and actions can increase employee engagement or even create an atmosphere where an employee becomes disengaged (feeling not part of the company/organization). In addition to marketing employees, rewards and recognition are generally used as the main motivation to improve their performance.For this reason, the purpose of this study is to determine the role of perceived supervisor support, rewards, and recognition, employee engagement on performance mediated by job satisfaction. The study was conducted with a survey using a questionnaire where respondents used 170 marketing employees in the banking industry in Tangerang. Data were analyzed using Structural Equation Model (SEM). The results showed there was a relationship between rewards and recognition of employee engagement, there was a relationship between rewards and recognition of performance, there was not a relationship between perceived supervisor support for performance. Employee engagement mediates the relationship between rewards and recognition of job satisfaction. Job satisfaction mediates the relationship between employee engagement on performance.